2022
DOI: 10.1002/admi.202200390
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating the Effect of Assay Media on the Rate of Virus Inactivation of High‐Touch Copper Surfaces: A Materials Science Approach

Abstract: Contamination of high‐touch surfaces with infected droplets of bodily secretions is a known route of virus transmission. Copper surfaces have been reported to inactivate human coronaviruses after several minutes, via the release of Cu cations. Utilization of copper alloys for high‐touch surfaces can be a pivotal preemptive strategy for preventing the next pandemic. Understanding the true efficacy by which copper, and copper alloys, inactivate the virus under realistic conditions is essential for tuning intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Indeed, we demonstrate that the different carrier solutions used in this study do influence the amount of copper ions released into solution from copper and Cu 2 O-containing surfaces, with the largest amount of copper ions released upon surface exposure to DMEM-2%FBS (tissue culture medium). In agreement with our observations, others have also reported that different liquids vary the level of ion release from copper and copper oxide surfaces and that the highest levels of release are into liquids containing amino acids, proteins or complex organic materials (4244). Some studies have reported a positive correlation between the amount of copper ion released from copper/copper surfaces and antibacterial activity (45).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, we demonstrate that the different carrier solutions used in this study do influence the amount of copper ions released into solution from copper and Cu 2 O-containing surfaces, with the largest amount of copper ions released upon surface exposure to DMEM-2%FBS (tissue culture medium). In agreement with our observations, others have also reported that different liquids vary the level of ion release from copper and copper oxide surfaces and that the highest levels of release are into liquids containing amino acids, proteins or complex organic materials (4244). Some studies have reported a positive correlation between the amount of copper ion released from copper/copper surfaces and antibacterial activity (45).…”
Section: Discussionsupporting
confidence: 93%
“…We envision that competition between biomolecules in the carrier solution and the surface of SARS-CoV-2 for copper ion complexation could explain why our copper surfaces perform better when virus inoculum is delivered in PBS (which forms liable weak copper complexes) compared to DMEM-2%FBS (which forms strong chelating complexes) and further would explain why we did not observe a clear positive correlation between level of copper ion release into solution and antiviral activity. In support, whilst our manuscript was being prepared Glover et al ., reported that coronavirus (OC43) inactivation on copper surfaces is significantly faster when virus was delivered in artificial perspiration solution compared to assay medium (DMEM) (44). Like our data, the rate of virus inactivation did not correlate with total amount of copper ions released into solution, instead they also suggest that chelated copper cations are not available for virus inactivation and that the organic constituents of DMEM act as chelators.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research has primarily focused on bacterial pathogens using Cu samples exposed to disinfectants and cleaning cloths not representative of those used in public venues and/or subjected samples to simulated use for relatively short periods (Bryce et al 2020 ; ISO 2022 ; EPA 2008 ). There has been some promising research demonstrating that Cu has excellent antiviral activity but studies are scarce and limited in terms of duration of simulated use with the appropriate disinfectants (Warnes and Keevil 2013 ; van Doremalen et al 2020 ; Warnes et al 2015 ; Glover et al 2022 ; Glass et al 2022 ; Mertens et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a phage‐guided nanohybrid system was constructed by combining azodibenzocyclooctyne (DBCO)‐modified dextran NPs with azide‐introduced phages in a culture media for 48 h (Zheng et al, 2019). However, it has been reported that Cu cations can inactivate viruses in a concentration‐dependent manner within several minutes (Glover et al, 2022). This led to the development of copper‐free click chemistry, which retains the favorable reaction rate and orthogonality underwater, while avoiding the disadvantages of traditional CuAAC (Yoon et al, 2022).…”
Section: Fundamentals Of Lvn Integrationmentioning
confidence: 99%